Передбачення статі дитини - Треб’єшанин, Ж. (Народна творчість та етнологія, 2012)
There are a lot of acts that the Serbians used to predict the sex of a child during pregnancy. The most frequent signs of the practice of sorcery are found in monitoring the changes in the external image and behavior of a pregnant woman. The rules for decoding these signs are based on the mythical-magic logic and the cultural tradition. Objects and parts of a body used to guess child sex, have the meaning of male/female symbols. Male symbols are: arms, knives, nose, etc; and female symbols are: scissors, mouth, etc. Attributes employed in the practice of sorcery of child sex are connected with opposition male/female. Males are: right up – vertical – long – pointy etc.; and females are: left–down–lay–round et.